Exploring flipped classroom integration with gamified applications for junior High school students - Hastomo, Tommy (Vestnik za tuje jezike, 2025)
Flipped classroom models have gained attention for promoting learner-centred instruction, mainly when supported by digital technology. In English as a Foreign Language (EFL) contexts, gamified applications such as Edpuzzle and Kahoot! have improved student engagement and motivation. However, limited research has examined how integrating gamified applications within flipped classrooms affects junior high school students’ learner autonomy, particularly in vocabulary learn-ing. This study aimed to investigate the level of learner autonomy among junior high school stu-dents after experiencing flipped instruction with gamified applications and to explore how this instructional model supports the development of autonomy. This study employed a qualitativemulti-site case study design, supported by descriptive quantitative data. The participants comprised five English teachers and 50 eighth-grade students from five junior high schools in Bandar Lam-pung, Indonesia. The researchers used two main instruments: a learner autonomy questionnaire and semi-structured group interviews. Data were collected after the implementation of flipped vocabulary instruction over 20 weeks, during which students engaged with Edpuzzle and Kahoot!. The questionnaire results were analysed using descriptive statistics with SPSS version 26, while interview data were analysed thematically. The findings revealed a consistently high level of learn-er autonomy across five domains. Thematic analysis identified three key themes supporting this de-velopment: self-paced learning, progress tracking, and continuous feedback. These results suggest that integrating gamified applications into flipped classrooms can promote student autonomy in vocabulary learning. The study recommends the broader adoption of the flipped teaching approach with gamified applications to foster independent learning among EFL student
Keywords: flipped classroom; gamified application; igrificirana aplikacija; junior high school; learner autonomy; nižja srednja šola; obrnjeno poučevanje, igrificirana aplikacija, nižja srednja šola, samostojnost učenca, učenje besedišča; samostojnost učenca; učenje besedišča; vocabulary learning